Extraction and identification of Conotoxins from several Conus collected in Nha Trang coast, Vietnam - Bich Thao, Le Thi; Binh, Doan Viet; Bich Nhi, Nguyen Thi; Chi, Phan Van (Academia Journal of Biology, 2012)
Venoms of Conus contain a cocktail of peptides that mainly target different voltage- and ligand-gated ion channels (commonly known as conopeptides or conotoxins), therefore they are classified as neuropeptides. Due to their extraordinary pharmacological properties, conopeptides gained increasing interest in recent years. We extracted and identified some conotoxins from eight Cone snails collected in Nha Trang coast (Vietnam): C. betulinus, C. caracteristicus, C. litteratus, C. Marmoreus, C. quericus, C. striatus, C. Textile and C. vexillum. Venoms from eight conus species were dissected and extracted. The extracted crude venoms were tested for analgesic activity on mice. On the hand, these crude venoms were initially separated on a Vydac C18 columm. The fractions were then separated on nanoLC chromatography system combined with tandem mass spectrometry to identify conotoxins. The results showed that venoms of eight Cone snails were found to produce analgesic activity in the formalin test and among them. The extracted crude venoms were tested analgesic activity on mice. The venoms of C. betulinus, C. vexillum, C. caracteristicus, C. textile and C. quericus gained higher analgesic activity than that of remained species. In each species, several toxic proteins/peptides were identified and the sequences of that are similar to toxic components of Conus species. The identified conotoxins were disulfide- rich conopeptides containing 4 or 6 cysteines based on published data.